The Portal Journal: its Contribution to the Conformation of the Chilean Cultural Field and the Debate around "the Latin American” 1965-1969 (Palimpsesto, 2020)
The 60's were a breeding ground for various disputes in the fields of culture and politics. Given this latency, various artists and intellectuals generated networks to disseminate and promote culture, literature and the arts; Thus, the cultural magazines of the time formed a territory of propositions and confrontations focused on establishing the role of the artist in front of his time and the tension between art and politics. Portal journal (1965-1969) and its proposal articulated by Marina Latorre, Eduardo Bolt and Luis A. Mancilla, is presented as central to the understanding and study of an era crossed by different narratives, where the concept of Latin American gains centrality.
Keywords: Cultural Journals; Political Field; Cultural Field; Latin America; Intellectuals